Conodontos del Viseense superior (Carbonífero) de la Unidad de la Sierra del Castillo (Córdoba, Espa - Bermúdez-rochas, David D.; Sarmiento, Graciela N.; Rodríguez, Sergio (Coloquios de Paleontología, 2004)
In the present work fifty seven samples were processed for searching conodont elements. Seventeen taxa of conodonts were identified, described and illustrated; they correspond to 8 genus, which are included in 5 families belonging to 2 orders, Ozarkodinida DZIK, 1976 y Prioniodinida SWEET, 1988. The Upper Visean (Carboniferous, Mississipian) studied sections are located near Espiel (Córdoba) in the Guadiato Area, in the Carboniferous basin from northern Ossa-Morena. The samples come from four of the five stratigraphical sections studied, that include about 300 meters of thickness: the sections of El Collado, Sierra del Castillo and Sierra de la Estrella 1 and 2. These sections, made up by the alternation of limestones and marls, are illustrated and the ranges of the recorded conodont taxa is provided. All the conodont elements are fragmented. The main identified taxa are: Gnathodus bilineatus (ROUNDY, 1926), G. praebilineatus BELKA, 1985, G. homopunctatus ZIEGLER, 1960, G. girtyi HASS, 1953, G. meischneri AUSTIN & HUSRI, 1974, G. pseudosemiglaber THOMPSON & FELLOWS, 1970, G. semiglaber BISCHOFF, 1957, Idioprioniodus healdi (ROUNDY, 1926), Idioprioniodus conjunctus (GUNNELL, 1931), Kladognathus spp., Bispathodus utahensis SANDBERG & GUTSCHICK, 1984, Lochriea commutata (BRANSON & MEHL, 1941), Vogelgnathus aff. postcampbelli (AUSTIN & HUSRI, 1974) and Mestognathus beckmanni BISCHOFF, 1957. This conodont assemblage could be indicative of the recognition of the Gnathodus bilineatus Zone (sensu BELKA, 1985) that comprises most Asbian and lower Brigantian stages (Upper Visean).